2017
DOI: 10.1039/c7fo01328k
|View full text |Cite
|
Sign up to set email alerts
|

Oral administration of lyophilizedDunaliella salina, a carotenoid-rich marine alga, reduces tumor progression in mammary cancer induced rats

Abstract: Dunaliella salina is a photosynthetic cell factory used for the commercial production of food additives, cattle stock feed and cosmetics as well as active ingredients for pharmaceutical industries. The investigation of the in vivo antitumor activity of D. salina lyophilized powder (DSLP) against 7,12-dimethylbenz(a)anthracene (DMBA) induced mammary carcinogenesis in female Wistar rats indicated a dose-dependent effect of DSLP. We studied the effect of DSLP at two different dosages of 500 and 1000 mg per kg bw … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 44 publications
1
18
0
Order By: Relevance
“…The results indicate that the dietary c 9, t 11‐CLA can significantly downregulate the hormonal receptor and has antiproliferative effect against mammary cancer in vivo. Similar result was also reported that the oral administration of Dunaliella salina powder can effectively reduce the PR and Ki‐67 levels in breast cancer‐induced animals (Srinivasan et al, ). Studies have demonstrated that many biomarkers, such as Ki‐67, caspases‐3, caspases‐9, Bax, and Bcl‐2, are associated with tumor cell proliferation and apoptosis.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…The results indicate that the dietary c 9, t 11‐CLA can significantly downregulate the hormonal receptor and has antiproliferative effect against mammary cancer in vivo. Similar result was also reported that the oral administration of Dunaliella salina powder can effectively reduce the PR and Ki‐67 levels in breast cancer‐induced animals (Srinivasan et al, ). Studies have demonstrated that many biomarkers, such as Ki‐67, caspases‐3, caspases‐9, Bax, and Bcl‐2, are associated with tumor cell proliferation and apoptosis.…”
Section: Resultssupporting
confidence: 78%
“…It was reported that the overexpression of PR was found in chemical carcinogen-induced mammary cancer SD rats (Simmen et al, 2005). In contrast, the ex- animals (Srinivasan et al, 2017). Studies have demonstrated that many biomarkers, such as Ki-67, caspases-3, caspases-9, Bax, and Bcl-2, are associated with tumor cell proliferation and apoptosis.…”
Section: Pr and Ki-67 In Mammary Tumorsmentioning
confidence: 99%
“…strain from the Tunisian coast identified to have 97% of similarity with Dunaliella salina [40]. Dunaliella salina is known for its high production of antioxidants, mainly β-carotene, which leads to its anticancer activity [4,5,[12][13][14][15][16][17]. D. salina is also able to produce hydrophilic compounds such as flavonoids, tannins and alkaloids [41].…”
Section: Discussionmentioning
confidence: 99%
“…The present study reports for the first time that Dunaliella aqueous holds an efficient antitumor activity against breast cancer cells growth both in vitro and in vivo by intratumoral injection. Previous reports related on the use of D. salina were performed with ethanolic extract or the whole powder with an oral administration requiring at least more than two weeks of treatments with high doses from 300 mg/kg up to 1000 mg/kg [2,4,5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation